Dietary Protein From Different Sources Exerted a Great Impact on Lipid Metabolism and Mitochondrial Oxidative Phosphorylation in Rat Liver - Shi, Xuebin; Huang, Zixin; Zhou, Guanghong; Li, Chunbao (Frontiers in Nutrition, 2021)
The associations between meat diets and human health have been widely concerned. In this work, we focused on the long-term effects of different sources of meat protein on liver metabolic enzymes. Rats were fed for 90 days semisynthetic diets that differed only with protein source. Casein was used as a reference and isolated soybean, fish, chicken, pork and beef protein were compared. Changes in liver proteome were performed using iTRAQ labeling and LC−ESI−MS/MS. Fish and pork protein diets upregulated the gene expression involving cholesterol synthesis and esterification, and pork protein diet also upregulated gene expression of high-density lipoprotein receptor and low-density lipoprotein receptor. Chicken, pork, and beef protein diets upregulated gene expression involving cholesterol reverse transport and bile acid production, which increased the total cholesterol level in fish protein diet group. The total cholesterol levels in liver were lower in pork and beef protein diet groups. The triglyceride levels in liver were lower in chicken, pork and beef protein diet groups. PGC1-α was upregulated by chicken, pork and beef protein diets, and promoted the degradation and metabolism of triglyceride, resulting in lower triglyceride in the three diet groups. Meat proteins at a recommended level could be more conducive to cholesterol degradation, triglyceride decomposition, and maintaining energy synthesis at a healthy level. The findings give a new insight into the associations between meat diet and human health.